Opportunities Following the Path to Sustainability at Universidad San Francisco de Quito - Espinoza, Camila; Proano-Alives, Juan (Journal of Sustainability Perspectives, 2024)
Since 2013, Universidad San Francisco de Quito (USFQ) has utilized various global and national sustainability assessment tools, including STARS by AASHE, UI Green Metrics, Q.S. Sustainability, and THE Impact Ranking. These tools have been pivotal in diagnosing institutional strengths and weaknesses, identifying opportunities for improvement, and integrating strategic actions into our policies and institutional plans. This paper explores the comparative effectiveness of these diverse sustainability evaluation tools and analyzes their impact on decision-making processes at USFQ. It explores how these assessments have informed our sustainability policies and strategies over the years, leading to significant improvements within our institution. Additionally, the paper presents successful case studies from USFQ where these tools have directly influenced the implementation of various projects. The insights provided will demonstrate how rigorous assessments can pave the way for meaningful institutional enhancements, offering a valuable resource for academic institutions worldwide to foster a culture of sustainability and make informed decisions that drive institutional change towards greater sustainability.